How can village midwives of the puskesmas work together with village administrator in eliminating malnutrition and preventing stunting: A case study in Tanjung Village, North Lombok - Astawan, Wanda Januar (BKM Public Health and Community Medicine, 2021)
How village midwives from puskesmas can become members of the work team of the village head in eliminating malnutrition and preventing stunting: a case study in Tanjung Village, North Lombok How village midwives from puskesmas can become members of the work team of the village head in eliminating malnutrition and preventing stunting: a case study in Tanjung Village, North Lombok Objective: To explore the role of village midwives as the implementing team for village government programs and health centers in developing strategies based on local conditions to reduce malnutrition and prevent stunting. Methods: Qualitative study with in-depth interviews, observation, document review, and journals related to the study of literature. Results: Tanjung Village is one of the villages that is the working area of ​​the Tanjung Health Center, which consists of 12 hamlets with a population of 8,287 people. The sources of income for the people of Tanjung Village are pretty diverse. The livelihoods of the Tanjung Village residents are dominated by 1,759 traders, 1,290 farm/construction workers, 1,149 farmers, 585 casual daily laborers, 450 farmers, and construction workers. Two hundred seventy-six people, 252 entrepreneurs, 170 fishers, 153 civil servants/TNI/POLRI/retirees, 16 craftsmen, ten mechanics, and the rest 2,476 people haven't worked. The implementation of health services for promotive, preventive, and curative efforts at the hamlet level in Tanjung Village is carried out in 12 posyandu in 12 hamlets carried out one time in 1 month. Each posyandu is assisted by five cadres, one village doctor, one nutritionist, and one village midwife. Promotive, preventive, and curative efforts have been made. Meanwhile, the prevalence of malnutrition is still above 30%, which is 34.56% of children under five. This is caused by the village midwife's approach to changing people's behavior for nutritional awareness is still less effective, coordination between implementing integrated stunting prevention programs such as village government and village midwives is still lacking, and adequate village midwife human resources with a reasonably high salary gap and weak government supervision. A village so that the implementation of the program does not run optimally. Conclusion: The program's implementation between the village midwife and the village government has not been well integrated. The need for village midwives to make local-based strategies and village government supervision and rewards to village midwives in program implementation to bring about change in alleviating malnutrition.